Sip1, the Drosophila orthologue of EBP50/NHERF1, functions with the sterile 20 family kinase Slik to regulate Moesin activity - Hughes, Sarah C. (Company of Biologists, 2010)
Organization of the plasma membrane in polarized epithelial cells is accomplished by the specific localization of transmembrane or membrane-associated proteins, which are often linked to cytoplasmic protein complexes, including the actin cytoskeleton. In this study, we identified Sip1 as a Drosophila orthologue of the ezrin-radixin-moesin (ERM) binding protein 50 (EBP50; also known as the Na(+)/H(+) exchanger regulatory factor NHERF1). In mammals, EBP50/NHERF1 is a scaffold protein required for the regulation of several transmembrane receptors and downstream signal transduction activity. In Drosophila, loss of Sip1 leads to a reduction in Slik kinase protein abundance, loss of Moesin phosphorylation and changes in epithelial structure, including mislocalization of E-cadherin and F-actin. Consistent with these findings, Moesin and Sip1 act synergistically in genetic-interaction experiments, and Sip1 protein abundance is dependent on Moesin. Co-immunoprecipitation experiments indicate that Sip1 forms a complex with both Moesin and Slik. Taken together, these data suggest that Sip1 promotes Slik-dependent phosphorylation of Moesin, and suggests a mechanism for the regulation of Moesin activity within the cell to maintain epithelial integrity.